2019
DOI: 10.1002/jqs.3113
|View full text |Cite
|
Sign up to set email alerts
|

Holocene evolution of the Indian Summer Monsoon inferred from a lacustrine record of Lake Wuxu, south‐east Tibetan Plateau

Abstract: A continuous sediment record since 12.3 cal ka bp from Lake Wuxu (south‐eastern Tibetan Plateau) was investigated in terms of the Holocene evolution of the Indian Summer Monsoon. The molar C/N ratio and stable C isotope were used to identify the source of the organic matter as well as climate conditions. The evolution of Lake Wuxu was summarized wihtin two periods. During the first period (early to mid‐Holocene), the lake received increased fluvially transported materials, reflecting variation in the summer mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 82 publications
(162 reference statements)
0
5
0
Order By: Relevance
“…The popularity of Bayesian techniques appears to be increasing. Yue Wang et al (2019) document a fairly consistent increase in citations of OxCal (Bronk Ramsey, 2008) and Bacon (Blaauw and Christen, 2011), although in many cases OxCal is used solely for 14 C age calibration and not model building. Half of the models in our literature sample relied on a Bayesian approach, with most of these built using Bacon (34%), rather than OxCal (14%) or Bchron (6%).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The popularity of Bayesian techniques appears to be increasing. Yue Wang et al (2019) document a fairly consistent increase in citations of OxCal (Bronk Ramsey, 2008) and Bacon (Blaauw and Christen, 2011), although in many cases OxCal is used solely for 14 C age calibration and not model building. Half of the models in our literature sample relied on a Bayesian approach, with most of these built using Bacon (34%), rather than OxCal (14%) or Bchron (6%).…”
Section: Introductionmentioning
confidence: 94%
“…Although Bayesian techniques use a different approach in the construction of age models, the ‘best-fit’ model can resemble simple linear interpolation e.g., when the mean age-depth model goes through each calibrated age range with changes in accumulation rate at dated depths. Resemblance to linear interpolation occurred in half (48%) of the Bacon models we examined (e.g., Yongbo Wang et al, 2019; McCulloch et al, 2019) and most if not all of the OxCal (e.g., Frodlová et al, 2018) and Bchron (e.g., Schiferl et al, 2018) models. Trachsel and Telford (2017) observed that “ although Bayesian age-depth modelling routines simulate changing accumulation rates, the mean accumulation rate (that is mostly used by scientists) is fairly constant between two dated levels, and therefore, the age-depth model is a straight line between two dated levels .” Similarity to linear interpolation is not altogether surprising, especially for Bacon and Bchron , as they are based in part on modelling piece-wise linear accumulations.…”
Section: Classical and Bayesian Age-depth Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the TP is one of the most sensitive areas to respond to global climate change (Liu and Chen, 2000). Therefore, the TP is an ideal site for studying the dynamics of the ASM (Zhou et al, 2010;Zhao et al, 2011;Cai et al, 2012;Bird et al, 2014;Zeng et al, 2017;Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These Lugu Lake is located on the southeast edge of the Qinghai-Tibet Plateau in Southwest China. The lakes in this area are tectonic lakes with fragile ecosystems, and can respond to environmental changes on scales from decades to millions of years (Chen et al, 2014;Wang et al, 2019). Magnetic measurement is a rapid, intensive, and non-destructive method to characterize high-resolution mineralogical changes, and is widely used in marine sequence comparison, paleoclimate, and provenance research (Peters et al, 2010;Chang et al, 2016;Wang et al, 2018aWang et al, , 2018b on lacustrine (Hu et al, 2015;Xu et al, 2020) and aeolian sediments (Gao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%